2019
DOI: 10.20884/1.jap.2018.20.3.742
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Human Being and Animal: The Study of the Concepts of Khalifah and the Animals in the Quran

Abstract: Islam does not only talk about the procedure of worshiping (ibadah), but also related to daily activities (muammalah), including how to treat animals. Understanding the relationship between human being and animals is the basis for further studies of animals in Islam. This study is library research using the descriptive-inferential method with the purpose to elaborate on the position of the animal against the human being based on the concept of the human being as khalifah. The Quranic verses about khalifah and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Research conducted by Ekowati and Setyadi found that livestock ownership has a positive effect on farmers' income [14]. This is in line with another research which emphasized that the increase in livestock business income was determined by the number of livestock ownership, which affected the amount of livestock to be sold and livestock business income [15,16].…”
Section: Number Of Goatssupporting
confidence: 64%
“…Research conducted by Ekowati and Setyadi found that livestock ownership has a positive effect on farmers' income [14]. This is in line with another research which emphasized that the increase in livestock business income was determined by the number of livestock ownership, which affected the amount of livestock to be sold and livestock business income [15,16].…”
Section: Number Of Goatssupporting
confidence: 64%
“…The former research stated that the narration of animals in the Quran can be divided into nine topics [1]. These nine topics can be summarized into three main points, namely animals as God's power, animals as creatures, and animals as beneficiaries for humans DOI 10.18502/kls.v0i0.11841 ICASI (Table 1).…”
Section: Conceptual Basic Underlying Animal Ethics In Islammentioning
confidence: 99%
“…Animals and humans are both living things with their eminence over each other. One of the human duties as God's vice-regent is to convey creatures towards their function of creation [1]. Animals are created as God's servant, community, and providing benefits to other creatures.…”
Section: Theology-based Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans possess both consciousness and self-awareness (Morin, 2006). Both concepts are explained in Alquran in the story of human creation (Safitri, Nuskhi, Muatip, Purwaningsih, & Setiana, 2019). Humans as subjects and objects are understood by learning about how they are created.…”
Section: Introductionmentioning
confidence: 99%